2014
DOI: 10.1007/s00253-014-6254-x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic humus and Fe(III) reduction and electron transport pathway by a novel humus-reducing bacterium, Thauera humireducens SgZ-1

Abstract: In this study, an anaerobic batch experiment was conducted to investigate the humus- and Fe(III)-reducing ability of a novel humus-reducing bacterium, Thauera humireducens SgZ-1. Inhibition tests were also performed to explore the electron transport pathways with various electron acceptors. The results indicate that in anaerobic conditions, strain SgZ-1 possesses the ability to reduce a humus analog, humic acids, soluble Fe(III), and Fe(III) oxides. Acetate, propionate, lactate, and pyruvate were suitable elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Similar microorganisms have been identified in groundwater bioremediation efforts as a result of organic carbon source addition (Liu et al, ; Zhang, Hao, et al, ). Thauera is able to reduce Fe (III) under anaerobic conditions (Ma et al, ). Rhodococcus in leachate‐contaminated soil can reduce Pb (IV) (Emenike et al, ), and Brevundimonas in subtropical paddy soils of China is known to participate in Fe (III) reducing processes (Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar microorganisms have been identified in groundwater bioremediation efforts as a result of organic carbon source addition (Liu et al, ; Zhang, Hao, et al, ). Thauera is able to reduce Fe (III) under anaerobic conditions (Ma et al, ). Rhodococcus in leachate‐contaminated soil can reduce Pb (IV) (Emenike et al, ), and Brevundimonas in subtropical paddy soils of China is known to participate in Fe (III) reducing processes (Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA-based Illumina sequencing results from PEM-HZ revealed that Dechloromonas , Thauera , Desulfovibrio and Clostridium were the most abundant bacterial species. These dominant species have been demonstrated to reduce Fe (III) of iron oxides via respiratory 6 7 8 19 20 21 . Thus, these species detected in PEM-HZ indicated a strong possibility that they were closely related to reducing Fe (III) of magnetite.…”
Section: Discussionmentioning
confidence: 99%
“…Thauera was also identied during the syntrophic oxidation of acetate and ethanol in paddy soil, 13,21 and has been described for its ability to reduce Fe(III) oxides using acetate and ethanol as electric donors under anaerobic conditions. 13,21,29 Thus, a high proportion of Thauera species identied in the SEM suggested that it was most closely related to reduction of Fe(III) in magnetite. Additionally, 16S rRNA-based Illumina sequencing of the archaeal community in the SEM revealed that Methanobacterium (11%) was the major dominant species, which utilizes H 2 and CO 2 to produce methane.…”
Section: Structure Of Microbial Communitiesmentioning
confidence: 98%